PERSEPSI MAHASISWA TERHADAP PROFESIONALISME DOSEN PROGRAM STUDI PENDIDIKAN BAHASA INGGRIS FKIP - Jonner Simarmata (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
Perception is an opinion, opinions, or perceptions of an event or phenomenon. The quality of a service that can be seen of how stakeholders or customers perceive the service. Professionalism is one form of service to stakeholders or customers. This study aimed to describe the students' perceptions of professionalism lecturer English Language Study Program Guidance and Counseling, University of Buffalo. To achieve this goal a questionnaire was distributed to 40 students (20% of the population). There are five aspects of the professionalism observed, namely: the ability to speak English, mastering the course material, teaching skills, work commitments, and breadth of vision. To analyze the data using a simple tabulation techniques. From the results of data analysis found that, as perceived by students, faculty English Language Study Program Guidance and Counseling, University of Buffalo has a high level of professionalism.Keyword : perception, professionalism, English education